Representations about institutional food by rural middle school boarding school students - Renata Gati Dalla Bernadina; Luciana Helena Maia Porte Porte (Universidade Federal do Norte do Tocantins, 2022)
Considering the importance of proper nutrition in adolescence and that this can be profoundly affected by changes in routine life of the students, such as leaving their home environment to live in a boarding school, the goal of this study was to analyze the social representation of these students in boarding school regime. A qualitative, exploratory research was carried out, based on the Theory of Social Representations. Individual interviews were conducted, and the discourse generated was analyzed using the Discourse of the Collective Subject technique. The representations of food, most of the interviewees considered that feeds well, and that high-quality food must have all the necessary nutrients; in addition, the change to the current institution have influenced the feeding times. The institutional foods were considered of good quality; however, the taste of the preparation has been mentioned as a negative point. The interviewees attributed the institutional food an important role in socialization, exerting positive influence on adaptation to boarding school.